Long Term Outcomes of Anterior Cruciate Ligament Reconstruction Surgery: 2020 OREF Clinical Research Award Paper - Fleming, Braden C. (J Orthop Res, 2020)
ACL injuries place the knee at risk for post-traumatic osteoarthritis (PTOA) despite surgical ACL reconstruction (ACLR). One parameter thought to affect PTOA risk is the initial graft tension. This randomized controlled trial (RCT) was designed to compare outcomes between two graft tensioning protocols that bracket the range commonly used. At 7-years post-surgery, we determined that most outcomes between the two tension groups were not significantly different, that they were inferior to an uninjured matched control group, and that PTOA was progressing in the both groups relative to controls. The trial database was also leveraged to gain insight into mechanisms of PTOA following ACL injury. We determined that the inflammatory response at the time of injury undermines one of the joint’s lubricating mechanisms. We learned that patients continue to protect their surgical knee 5 years post-injury compared to controls during a jump-pivot activity. We also established that pre-surgical knee function and mental health were correlated with symptomatic PTOA, that there were specific anatomical factors associated with poor outcomes, and that there were no changes in outcomes due to tunnel widening in patients receiving hamstring tendon autografts. We also validated an MRI technique to non-invasively assess graft strength. In conclusion, the RCT determined that initial graft tensioning does not have a major influence on 7-year outcomes. Therefore, surgeons can reconstruct the ACL using a graft tensioning protocol that is within the window of the two graft tensioning techniques evaluated in this RCT.